ANALISIS TRANSPARANSI DAN AKUNTABILITAS PENGELOLAAN ALOKASI DANA DESA (ADD) (Studi Kasus Pada Desa Bukit Pariaman Kecamatan Tenggarong Seberang Kabupaten Kutai Kartanegara) - -, Nining Sumarni (EKONOMIA, 2019)
This study aims to determine whether in Bukit Pariaman Village, Tenggarong District across Kutai Kartanegara District in the management of Village Fund Allocation from 2015-2017, it has been carried out transparently and accountably in accordance with the Regulation of the Minister of Home Affairs Number 113 of 2014 Article 2 paragraph 1.The basic theory used in this study is public sector financial management that focuses on transparency and accountability in financial management, especially the management of Village Fund Allocation (ADD). This research hypothesis is the Management of Village Fund Allocation (ADD) in Bukit Pariaman Village, Tenggarong District across Kutai Kartanegara District, which has been carried out transparently and accountably.The analytical tool used is an analytical tool for transparency and accountability in managing Village Fund Allocation.The results showed that the Management of Village Fund Allocation (ADD) in Bukit Pariaman Village in 2015-2017 had been carried out transparently and accountably with iinterval answers 1.9 (transparency) and 1.96 (accountability) so that the hypothesis in this study was accepted